2017
DOI: 10.1177/2048872617741735
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary trends in cardiogenic shock: Incidence, intra-aortic balloon pump utilisation and outcomes from the London Heart Attack Group

Abstract: Cardiogenic shock treated by percutaneous coronary intervention is increasing in incidence and remains a condition associated with high mortality and limited treatment options. Intra-aortic balloon pump therapy was not associated with a long-term survival benefit in this cohort and may be associated with increased early morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1
15

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 41 publications
9
77
1
15
Order By: Relevance
“…A major shift in the choice of mechanical circulatory support device occurred over the years with an almost complete abandonment of IABP and a concomitant increase in the use of Impella (a transvalvular axial flow pump) and VA‐ECMO. Previous studies have also reported a decline in the use of IABP over time but our study demonstrates a near complete elimination of IABP use, and this change coincides with the publication of the results of the IABP‐SHOCK II trial . In line with previous studies reporting increased use of VA‐ECMO and Impella, we observed increased use of Impella device, reaching a plateau at ∼16% in 2016–2017 compared to 3–4% as reported previously .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A major shift in the choice of mechanical circulatory support device occurred over the years with an almost complete abandonment of IABP and a concomitant increase in the use of Impella (a transvalvular axial flow pump) and VA‐ECMO. Previous studies have also reported a decline in the use of IABP over time but our study demonstrates a near complete elimination of IABP use, and this change coincides with the publication of the results of the IABP‐SHOCK II trial . In line with previous studies reporting increased use of VA‐ECMO and Impella, we observed increased use of Impella device, reaching a plateau at ∼16% in 2016–2017 compared to 3–4% as reported previously .…”
Section: Discussionsupporting
confidence: 91%
“…Contemporary data regarding incidence, patient characteristics, management, and outcome are limited. They are based on registries using diagnosis codes of ST‐elevation myocardial infarction (STEMI) and report conflicting results regarding incidence, mortality, co‐morbidity burden, and use of mechanical circulatory support devices . The temporal trends in the proportion of patients with out‐of‐hospital cardiac arrest (OHCA) have not been reported, but likely increased as more patients with OHCA survive to hospital admission in recent years .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiogenic shock (CS) complicates 5% to 10% of cases with acute myocardial infarction (AMI) and remains the leading cause of death in patients with AMI . The Should We Emergently Revascularize Occluded Coronaries for Cardiogenic Shock (SHOCK) trial demonstrated improved short‐ and long‐term survival with early revascularization in patients with AMI and CS (AMICS) .…”
Section: Temporal Trends In Incidence Revascularization and Mortalimentioning
confidence: 99%
“…The Should We Emergently Revascularize Occluded Coronaries for Cardiogenic Shock (SHOCK) trial demonstrated improved short‐ and long‐term survival with early revascularization in patients with AMI and CS (AMICS) . Although rates of early coronary angiography in patients with AMICS have increased over the past two decades, only 60% to 70% of patients undergo early revascularization . Further, in AMICS patients undergoing early revascularization, the use of intra‐aortic balloon pump (IABP) failed to demonstrate reduction in 30‐day mortality in the IABP‐SHOCK II trial .…”
Section: Temporal Trends In Incidence Revascularization and Mortalimentioning
confidence: 99%
See 1 more Smart Citation